PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA MENGGUNAKAN METODE PERCOBAAN DI SEKOLAH DASAR - Susilawati, Roberta; Rosnita, Rosnita; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the improvement of students’ learning outcomes using experiment method in learning science.The method of this research is descriptive in form of classroom action research. The subject of this research is teacher and fourth grade students that is thirteen students of Sekolah Dasar Negeri 10 Senangak Kabupaten Bengkayang.Technique of data collecting is direct observation and document analysis. Technique of data analysis is by calculating the mean and percentage. This research is done in three cycles with the result: (1) teacher’s ability on planning is 3.35 in the first cycle, 3.61 in the second cycle, and 3.84 in the third cycle; (2) teacher’s ability on implementing is 2.95 in the first cycle, 3.56 in the second cycle, and 3.82 in the third cycle; (3) the students’ learning outcomes is 48,46 with 38.46% students who passed the test in the first cycle, 57.69 with 61.54% students who passed the test in the second cycle, and 62.30 with 69.23% students who passed the test in third cycle. In conclusion, using experiment method in learning science can improve students’ learning outcomes. Keywords: Experiment Method, Learning Outcomes, Science